Influences of sol-gel derived thin Pb(Zr0.52Ti0.48)O-3 layers as a buffer on RF sputtered Pb(Zr0.52Ti0.48)O-3 thin films - Kim, TS; Kim, JH; Lee, JK; Jung, HJ (GORDON BREACH SCI PUBL LTD, 1995)
PZT(52/48) films are deposited by using an off-axis rf magnetron sputtering method on Pt/Ti/SiO2/Si(100) substrate. In order to decrease the microcracks which occurs on the surface of rf sputtered PZT films during postannealing at 600, 650 and 700 degrees C, sol-gel derived 10% Pb excess Pb(Zr0.52Ti0.48)O-3 layers are placed at the top and bottom of the rf sputtered PZT films, respectively. SEM micrographs reveal a drastic reduction of microcracks on the surface of the buffered PZT films. In addition, enhancement of crystallinity is also observed according to XRD analysis. The P-E hysteresis measurements show an increase in remanent polarization (12.1, 22.45, 34.64 mu C/cm(2)) and a decrease of the coercive field (108, 72.9, 68.3 kV/cm) with the increase of post-annealing temperature.
Keywords: ZIRCONATE